DataGramaZero Vol. 15, n. 1 (2014) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2014)
DataGramaZero Vol. 15, n. 1 (2014) Link de acesso ao númerohttp://dgz.org.br/fev14/F_I_aut.htm